2004
DOI: 10.1097/00003226-200403000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Therapy on the Recovery and Frequency of Corneal Pathogens

Abstract: There is a delay in starting microbiologic-guided antibiotic treatment in patients who have received empiric therapy. Nonbacterial corneal pathogens may be associated more frequently with patients on prior therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 7 publications
1
25
1
1
Order By: Relevance
“…This contrasted with a study by Marangon et al, 42 which found that there was no statistical difference in culture yield in patients using antibiotics versus those who were not. However, patients using therapy were more likely to have a delay in pathogen recovery and to have resistant pathogens.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This contrasted with a study by Marangon et al, 42 which found that there was no statistical difference in culture yield in patients using antibiotics versus those who were not. However, patients using therapy were more likely to have a delay in pathogen recovery and to have resistant pathogens.…”
Section: Discussioncontrasting
confidence: 81%
“…However, patients using therapy were more likely to have a delay in pathogen recovery and to have resistant pathogens. 42 The outcomes of patients with corneal involvement in this study were encouraging. There was no case requiring surgical intervention, as compared with other studies of pediatric microbial keratitis in which the operative rates varied from 6% to 28%.…”
Section: Discussionmentioning
confidence: 60%
“…Most previous studies have not demonstrated a significantly lower culture yield for corneal ulcers in patients previously treated with topical antibiotics, although bacterial growth may be delayed. 15,18,[25][26][27] Based on our findings, we strongly advocate the use of smear microscopy on the day of presentation to guide initial antimicrobial therapy. In tertiary referral centers in this region of the world, the treating physician should consider early initiation of topical antifungal agents as empiric therapy for severe corneal ulcers, particularly if known risk factors are identified.…”
Section: Discussionmentioning
confidence: 79%
“…The excessive use of antibiotic agents is a primary cause of resistance, as shown in a study that found a greater incidence of multidrugresistant bacteria and a slower rate of healing in patients with keratitis who were pretreated with an antibiotic than in patients who did not receive pretreatment. 59 Physicians should select agents that have rapid bactericidal activity, high attainable concentrations at the site of infection compared with the organism MIC, a relatively low incidence of antibacterial resistance, and a broad spectrum of activity. The newer fluoroquinolones, for example, fulfill these criteria, whereas chloramphenicol and the sulfonamides are no longer used in the U.S. because of the development of resistance.…”
Section: Guidelines For Minimizing Ocular Pathogen Resistancementioning
confidence: 99%